Time-varying impact of pandemics on global output growth - Gupta, Rangan; Sheng, Xin; Balcilar, Mehmet; Ji, Qiang (Academic Press Inc Elsevier Science, 2021)
This paper analyses the dynamic impact of uncertainty due to global pandemics (SARS, H5N1, H1N1, MERS, Ebola, and COVID-19) on global output growth, using a TVP-SVAR model. We find that the negative effect of the coronavirus on the growth rate of output is unprecedented, with the emerging markets being the worst hit. We also find that since 2016, the comovement among the growth rates has increased significantly. Our results imply that policymakers would need to undertake massive expansionary policies, but it is also important to pursue well-coordinated policy decisions across the economic blocs.
Keywords: Pandemics; Uncertainty Output growth TVP-SVAR